Sustainable education development (assess the impact of schooling programs) / Eko Sriyanto, Pedri Hariyadi and Masykur Huda - Sriyanto, Eko; Hariyadi, Pedri; Huda, Masykur (2023)
Lembaga Pengembangan Insani (LPI DD) is one of Dompet Dhuafa's organs that focuses on education programs. In managing education programs, LPI DD also monitors the achievement of the organization's vision and mission. Therefore, many studies are conducted to obtain more effective and efficient evaluations. Impact assessment is one of the models for measuring school programs managed by LPI DD. This study was conducted through three school programs; Sekolah Guru Indonesia (SGI), Sekolah Literasi Indonesia (SLI), and Komunitas Media Pembelajaran (KOMED). This study aims to identify the impact of the implementation of LPI DD's school programs on the improvement of the competence and well-being of beneficiaries. This impact assessment uses a descriptive analytic approach with quantitative research methods, including literature reviews and questionnaire surveys. A total of 265 respondents from 27 provinces, with ages ranging from 18 to over 61 years and gender of male (32.8%) and female (67.2%), were involved in this study. The results of the study showed that LPI DD's school programs had a significant impact on increasing the well-being of respondents in both material and spiritual aspects. CIBEST analysis showed that there was a change in the number of respondents in the first quadrant category (well-being condition), which was 36.98% before the implementation of the program to 70.19% after the program. In addition, the program also provided positive changes (most significant change story) to 94.3% of respondents and 93.4% of respondents experienced a turning point. It is also known that most beneficiaries contribute to society after participating in the program. Thus, the transformation that occurred was not only in the individual aspect but also in the social aspect. This study contributes to school programs by encouraging the emergence of innovative alternative education ideas that are expected to provide valuable insights for policymakers, practitioners, and researchers working towards sustainable education improvement.